Estimating the Assist Map of Electro-Hydraulic Power Steering System for an Electric Microbus - Perdana, Muhammad Arjuna Putra; Ristiana, Rina; Mardiati, Rina; Kaleg, Sunarto; Muharam, Aam; Amin (International Conference on Wireless and Telematics (Online), 2024)
The Electro-Hydraulic Power Steering (EHPS) system relies on an assist map to calculate the assist torque based on various vehicle parameters. The assist map characteristic determines the assist torque value depending on the vehicle's longitudinal speed, vehicle lateral acceleration, EHPS motor speed, and steering wheel torque. The interaction between the variables is then depicted in a three-dimensional map that guides the EHPS assist. To avoid interference with the steering system's performance, an Extended Kalman Filter (EKF) approach was added to the nonlinear system to ensure good system response and accuracy under the influence of random noise. The assist map is calculated using variations in steering drive torque, vehicle lateral acceleration, and EHPS motor speed when the vehicle is stationary or at zero speed. In the future, the assist map will be integrated into the EHPS system to support the driver in steering at various speeds.